Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

The average of a, b and c is (a + b + c)/3. So, basically to answer the question we need to know the value of a + b + c.

(1) The average of a and b is c --> (a + b)/2 = c --> a + b = 2c. Not sufficient.

(2) The average of b and c is 4 --> (b + c)/2 = 4 --> c = 8 - b. Not sufficient.

(1)+(2) We have that a + b = 2c and c = 8 - b, thus a + b + c = 2c + c = 3c = 3(8 - b). Without knowing the value of c or b we cannot get this value. For example, consider a = 1, b = 5, c = 3 or a = 4, b = 4 and c = 4. Not sufficient.

(1) The average of a and b is c. (2) The average of b and c is 4.

Target question:What is the average of a, b, and c? NOTE: since the average = (a+b+c)/3, our goal here is to find the SUM a + b + c

So, we can REPHRASE the target question.... REPHRASED target question:What is the value of a + b + c?

Statement 1: The average of a and b is c This means that (a + b)/2 = c Multiply both sides by 2 to get: a + b = 2c There are several values of a, b, and c that satisfy statement 1. Here are two: Case a: a = 1, b = 1 and c = 2, in which case a + b + c = 1 + 2 + 2 = 5 Case b: a = 1, b = 2 and c = 3, in which case a + b + c = 1 + 2 + 3 = 6 Since we cannot answer the REPHRASED target question with certainty, statement 1 is NOT SUFFICIENT

Statement 2: The average of b and c is 4 Since there's no information about a, there's no way to find the value of a + b + c Since we cannot answer the REPHRASED target question with certainty, statement 2 is NOT SUFFICIENT

Statements 1 and 2 combined Statement 1 tells us that a + b = 2c Statement 2 tells us that (b + c)/2 = 4, which means b + c = 8

So, we have the following system: b + c = 8 a + b = 2c

IMPORTANT: Many students will look at this system and incorrectly conclude that, since we have 2 equations and 3 variables, there's no way to answer the target question. This is not necessarily the case, because the target question does NOT ask us to find the individual values of a, b and c. The target question asks us to find the SUM of a, b, and c. So, for example, if the two equations happened to be a + b + 2c = 5 and 2a + 2b + c = 19, then we could ADD the equations to get 3a + 3b + 3c = 24, and upon dividing both sides by 3, we'd see that a + b + c = 8, in which case we COULD answer the target question despite only having 2 equations with 3 variables. So, we can't just automatically assume that we don't have sufficient information.

So, let's TEST some values of a, b and c that satisfy BOTH equations.

NOTE: since the equation b + c = 8 doesn't have the variable a, let's use it to first find some values of c and b, then we'll use the other equation, a + b = 2c, to find the corresponding a value.

Case a: b = 1 and c = 7 satisfies the equation b + c = 8 . Now plug these values into the other equation (a + b = 2c) to get: a + 1 = 2(7). Solve to get: a = 13. So, the values are a = 13, b = 1 and c = 7, which means a + b + c = 13 + 1 + 7 = 21 Case b: b = 0 and c = 8 satisfies the equation b + c = 8 . Now plug these values into the other equation (a + b = 2c) to get: a + 0 = 2(8). Solve to get: a = 16. So, the values are a = 16, b = 0 and c = 8, which means a + b + c = 16 + 0 + 8 = 24 Since we cannot answer the REPHRASED target question with certainty, the combined statements are NOT SUFFICIENT